The impacts of different types of workload allocation models on academic satisfaction and working life - Vardi, Iris (Springer, 2009)
Increasing demands on academic work have resulted in many academics working long hours and expressing dissatisfaction with their working life. These concerns have led to a number of faculties and universities adopting workload allocation models to improve satisfaction and better manage workloads. This paper reports on a study which examined the workload models in use across a large Australian university. Analysis revealed that the various models could be categorised into three types. The pros, cons and impacts of these three categories of model were compared from both a management and staff perspective. The study found that while models of all types can lay the foundation for equitable distribution of workload, some categories of model can have unintended consequences with negative effects on the work culture and hence staff satisfaction.